‘We Pay to Buy Ourselves’: Netflix, Spectators & Streaming - Rodríguez Ortega, Vicente (The Journal of communication inquiry, 2023)
This article explains how Netflix has transformed the ways in which we interact with media in the contemporary milieu. I argue that Netflix works through a process of planned differentiation, designing unique customization experiences to create a new type of media user that participates in its global and regional release and production strategies. This leads me into a discussion of how the Netflix interface manages the spectators’ experience through a series of connected features. Thus, I detail Netflix’ personalization mechanisms, proposing that, ultimately, its users ‘pay to buy themselves’, or the version of themselves its interface offers back to users upon systematically gathering data on their habits. Finally, I remark that the key characteristics of the current streaming service/spectator relationship are deceptive limitlessness, customization, the automation of content flow and ubiquity, weaving a form of audiovisual engagement that has partially and, at times completely, conquered our everyday.